A NEW LEVEL OF ENSURING ROAD TRAFFIC SAFETY IN UZBEKISTAN (European Journal of Interdisciplinary Research and Development, 2022)
The main purpose of the law is to ensure, firstly, the protection of life and health of citizens, secondly, their rights and legal interests, thirdly, the property of legal entities and individuals, and fourthly, the protection of the environment by regulating relations in the field of road safety.